Rapid diagnostic testing to improve access to screening for syphilis in prison - K Montaño; A Flores; M Villarroel-Torrico; N Cossio; A Salcedo-Meneses; C Valencia-Rivero; R Castro-Soto; G Gétaz-Jiménez; H Wolff; H Bermúdez-Paredes; L Gétaz
ABSTRACT Objectives To assess the accuracy of on-site rapid treponemal test for syphilis diagnosis in women deprived of liberty in Bolivia. Material and methods Serological tests for syphilis were performed on 219 women deprived of liberty from the San Sebastián prison in Cochabamba, Bolivia. Syphilis was diagnosed using RPR (bioMérieux) and TPPA (Fujirebio) serological tests, and the results were compared to on-site rapid treponemal test (Alere DetermineTM Syphilis TP) in whole blood. Diagnostic performance of two FTA tests were also compared (bioMérieux and Biocientífica). Results All participants (28) with RPR+/TPPA+ had the rapid syphilis test positive (sensitivity 100%). Eleven participants had rapid syphilis test positive without RPR and TPPA both positive; nevertheless 7 of them had RPR or TPPA positive. Of 33 participants with FTA-bioMérieux positive, 22 (66.6%) had FTA-Biocientífica positive. Discussion The rapid syphilis test Determine shows excellent performance as a screening tool among women deprived of liberty affected by high prevalence of syphilis. This test is particularly indicated when there are barriers for access to conventional serological tests. It is inexpensive, easy to use and does not require electricity and laboratory infrastructure. The FTA test performed with reagents from Biocientífica had a suboptimal sensitivity.